The Effectiveness of Mathematical Learning Based on WhatsApp Groups Assisted by LKPD and Student’s Motivation - Putri, Laras Eprilia; Arigiyati, Tri Astuti; Taufiq, Irham (Universitas Sarjanawiyata Tamansiswa, 2022)
This research is a quasi-experimental research that aims to determine whether online learning based on WhatsApp Group with LKPD assistance is more effective than with-based online learning WhatsApp Group without the assistance of LKPD in terms of student learning motivation towards mathematics learning outcomes of class VII students at SMP Negeri 3 Jetis. The data analysis technique used t-test, prerequisite test in the form of normality test and homogeneity test, Mann-Whitney test, and Kruskal Wallis test. The result of this study is that online learning based on WhatsApp Group with the assistance of LKPD is as effective as online learning based on WhatsApp Group without the assistance of LKPD and the mathematics learning outcomes of students with high motivation are better than students with moderate and low motivation.